Simulation of flow and thermal comfort zones in a Thai state school - Nitatwichit C. (2014)
Most classrooms of Thai state primary schools are designed to use cross-flow natural ventilation as a passive cooling system. The aim of this study is to investigate the effects of geometry and orientation of school buildings to indoor airflow distribution and thermal comfort in typical state school classrooms. Computational fluid dynamics commercial software was used as a tool in this simulation. Local meteorological conditions and measured data at a real building were employed as the boundary conditions. The airflow simulation for building domains was performed with reference to the prevailing wind. Wind speeds and directions close to openings were averaged and used to represent the inlet boundary conditions of the classroom domains. Manikins and desks were included in the classroom domains. The simulation was carried out, focusing on a comfortable indoor thermal environment for the occupants. Simulated results revealed that an orientation of a school building normal to wind direction might not always be necessary to obtain a thermally comfortable environment in a classroom. Main inlet flow from openings was not found to affect the students directly. However, a comfortable feeling was possible within the occupied zone in winter when ambient temperature was low. Operative temperatures were also within 90% acceptability limits, according to the adaptive comfort standard. © 2012 The Chinese Institute of Engineers.